Intrapleural Thrombolytics as First Line Therapy for Complicated Parapneumonic Effusions and Empyema in Patients with Prohibitive Surgical Risk: A Cases Series - Morales-Colón, Sulimar; Rivera-Agosto, Mariela M.; Mercader-Pérez, Mariana; Cantres-Contreras, Onix; Rodríguez-Cintrón, William (Puerto Rico Health Sciences Journal, 2023)
Objective: In complicated parapneumonic effusion or Empyema, approximately 25% of patients require surgical intervention which can be associated with a mortality risk of almost 20%. However, the use combination of rt-tPA and DNase in elderly patients with prohibitive surgical risk has improved outcomes. The main goal of our study is to highlight the utility of intrapleural thrombolysis in patients with prohibitive risk for surgery. Methods: A retrospective record review study of patients (n=23) with complicated parapneumonic pleural effusion or empyema treated with tPA and DNase from January 1st of 2015 to March 18th, 2019 at VACHCS. Data collected to describe the outcome of intrapleural thrombolytics included demographic, pleural fluid analysis, surgical risk assessment, diagnosis and initiation treatment day, doses, chest imaging, drainage rate, chest tube size and average days in place, inflammatory markers, microbiology, antibiotics, and complications. Results: Only 21.7% of patients were considered surgical candidates. Seventy-four percent had a 30-day post-surgical mortality risk of > 2.5% using the National Surgery Office (NSO) risk calculator. Post-operative inpatient stay was 99.7% and estimated post operative ICU stay average was >80%. Primary outcome (pleural drainage improvement) obtained in 73.9%. Most common serious complications included sepsis (52.2%) and nonserious was residual hydropneumothorax (47.8%). Conclusion: This study demonstrates that administration of intrapleural thrombolytics through a percutaneous pleural catheter achieved successful drainage safely and without the need for surgical interventions in a selected group of advanced age, elderly patients with pleural infections who were deemed to be high surgical risk.